Active surveillance for acute flaccid paralysis in poliomyelitis high-risk areas in southern China - Chiba Yasuo; Hikita Kazuo; Matuba Tsuyoshi; Chosa Tooru; Shinji Kyogoku; Jingjian Yu; Zhao Wang (The World Health Organization, 2001)
OBJECTIVE: On 29 October 2000 poliomyelitis was officially declared to have been eradicated from the Western Pacific Region. This article describes the results of surveillance for cases of acute flaccid paralysis (AFP) in China during the final phase of the eradication effort. METHODS: We conducted hospital-based active surveillance in high-risk areas for poliomyelitis in 5 provinces of southern China (Sichuan, Yunnan, Guizhou, Guangxi and Jiangxi) between 1995 and 1997 to determine the adequacy of reporting and laboratory diagnosis of cases of AFP. FINDINGS: A total of 1069 AFP cases occurring since 1993 were identified in 311 hospital visits. Less than 50% of AFP cases occurring in 1993 and 1994 had been reported by AFP surveillance, and laboratory diagnosis had been carried out on only a small proportion of these. However, improved cooperation between hospital sectors increased the rate of case reporting and laboratory diagnosis to 85% and 78%, respectively, in 1997. Despite this overall improvement, these two indicators were approximately 10-20% lower in Yunnan Province. Epidemiological analysis revealed that cases of clinical poliomyelitis accounted for as much as one-third of all AFP in 1993 and that some of these cases were clustered. Clusters were rarely observed after 1994. Active surveillance in the China-Myanmar border areas of Yunnan over 1995-96 detected 9 cross-border cases of clinical poliomyelitis, including 2 of wild poliomyelitis. Import of poliomyelitis was thus considered to have occurred frequently until 1996 in this border area of Yunnan. These data were important for the outbreak response immunization carried out in 1996 in the border prefectures of Yunnan. CONCLUSION: Our investigation confirmed a high level of AFP surveillance in poliomyelitis high-risk areas of the five provinces and provided valuable information on the interruption of wild poliovirus circulation in southern China that will be of use to countries in other regions that have yet to eradicate poliomyelitis.